1985
DOI: 10.1113/jphysiol.1985.sp015684
|View full text |Cite
|
Sign up to set email alerts
|

Action and localization of gamma‐aminobutyric acid in the cat retina.

Abstract: The effects of iontophoretically applied GABA (gamma‐aminobutyric acid) and bicuculline on retinal ganglion cells were studied in the optically intact eye of the anaesthetized cat. GABA suppressed both the spontaneous activity and light‐evoked discharge of all retinal ganglion cells, regardless of their type and regardless of the visual stimulus used. Bicuculline antagonized the action of iontophoretically applied GABA. Bicuculline enhanced the spontaneous activity of on‐centre cells, but suppressed the sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 54 publications
9
39
1
Order By: Relevance
“…Transient peak responses always seem to be more resistant to drug action than tonic discharge (Sillito & Kemp, 1983). Our results with bicuculline application in off-centre cells (Bolz et al 1985) indicate that the same drug can dramatically increase the peak discharge and at the same time decrease the tonic part of the histogram. The comparison of strychnine and bicuculline action on the same off-centre cell in Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Transient peak responses always seem to be more resistant to drug action than tonic discharge (Sillito & Kemp, 1983). Our results with bicuculline application in off-centre cells (Bolz et al 1985) indicate that the same drug can dramatically increase the peak discharge and at the same time decrease the tonic part of the histogram. The comparison of strychnine and bicuculline action on the same off-centre cell in Fig.…”
Section: Discussionmentioning
confidence: 51%
“…These results are consistent with other studies that measured the receptive field of mammalian ganglion cells at photopic light levels. Frishman and Linsenmeier (1982) showed that picrotoxin had little effect on the surrounds of cat X and Y ganglion cells, and Bolz et al (1985) found that the application of neither GABA nor the GABA A receptor antagonist bicuculine affected the center-surround balance of cat ganglion cells. In a series of experiments, Daw and Ariel (1981) showed that picrotoxin did not eliminate the surround of any of the rabbit center-surround ganglion cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the uptake of tritiated GABA or muscimol [1,2] and immunocytochemistry with antibodies against glutamic acid decarboxylase (the GABA-synthesizing enzyme GAD) or against GABA [3,4] showed that, next to glycine, GABA is the predominant transmitter of amacrine cells in the mammalian retina. Amacrine cells of rat, cat and most animal species contain GAD.…”
Section: Introductionmentioning
confidence: 99%